Drought dynamics and interannual rainfall variability on the Ghaap plateau, South Africa, 1918–2014 - Dlamini, P. E. (Physics and Chemistry of the Earth, 2018)
With drought expected to increase in frequency and severity as a result of climate change, drought and rainfall variability assessments at interannual time scales using long-term rainfall data are necessary to develop drought mitigation strategies and planning measures, especially in semi-arid and arid environments where drought impact is expected to be adverse. The objective of this study was to determine the occurrence and severity of droughts and interannual rainfall variability trends in the Ghaap plateau, Northern Cape Province, South Africa. This study was based on long-term rainfall data for three meteorological stations (Postmasburg, Douglas and Groblershoop) from 1918 to 2014, sourced from the South African Weather Services (SAWS). Calculation of the Standardized Precipitation Index (SPI) showed that more droughts occurred since the 1990s; these droughts were all moderately dry with SPI values ranging between −1.03 and −1.46, except for the 1992 drought at Groblershoop which was severe. The longest drought duration on record in the study area was 2 years. Fitting of the long-term rainfalldatatoanon-parametric spline smootherrevealed thatthe totalannual rainfall, numberof rainfall days and extreme rainfall events were essentially stable. The total annual rainfall, however, followed a secular pattern of ﬂuctuations over the years.
Article published in the Physics and Chemistry of The Earth · September 2018 DOI: 10.1016/j.pce.2018.09.003
Keywords: Drought; Standardized precipitation index; Interannual rainfall variability; Spline smoother; Ghaap plateau; Drought forecasting -- South Africa